Managing Insecticide and Miticide Resistance in Florida Landscapes - Nicole Benda; Adam G. Dale (EDIS)
Resistance to insecticide or miticide is a worry for landscape managers. Around the world, chinch bugs, leafminers, and other insect and mite pests have become resistant to dozens of insecticides, but with diligent insecticide resistance management, we can still maintain long-term effective chemical control. With few new modes of action coming onto the market, landscape managers need to be good stewards of existing products. Ultimately, resistance management means reducing exposure of pests to any one pesticide. Fortunately, there are many ways to prevent resistance and still control pests of ornamental plants and lawns, and this 6-page fact sheet written by Nicole Benda and Adam Dale and published by the UF/IFAS Entomology and Nematology Department explains how. http://edis.ifas.ufl.edu/in714